Dummy trajectory privacy protection scheme for trajectory publishing based on the spatiotemporal correlation - Kai-yue LEI; Xing-hua LI; Hai LIU; Zhuo-xiong PEI; Jian-feng MA; Hui LI (Tongxin xuebao)
The spatiotemporal correlation was analyzed between neighboring locations and the trajectories similarity from the movement direction, the reachable time between neighboring locations and the movement distance, and a dummy trajectory privacy protection scheme based on the spatiotemporal correlation was proposed. Security analysis shows that the presented scheme successfully confuses the user's real trajectory with dummy trajectories, thereby pro-tecting the user's trajectory privacy. Furthermore, extensive experiments indicate that the presented scheme not only has the limited computation cost, but also ensures that the generated dummy trajectories are similar to the user's real trajectory.